1996
DOI: 10.1097/00007632-199601010-00017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lumbar Spine and Hip Motion During Forward Bending in Subjects With and Without a History of Low Back Pain

Abstract: The results provide quantitative data to guide clinical assessment of forward bending motion. Results also suggest that although people with a history of low back pain have amounts of lumbar spine and hip motion during forward bending similar to those of healthy subjects, the pattern of motion is different. It may be desirable to teach patients with a history of low back pain to use more hip motion during early forward bending, and hamstring stretching may be helpful for encouraging earlier hip motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
269
4
13

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(309 citation statements)
references
References 17 publications
23
269
4
13
Order By: Relevance
“…The relative lumbar/pelvic rotations during lowering/ lifting phases showed greater contributions in all cases from the pelvis than the lumbar spine (by as much as twofold) and remained within the range of data reported in the literature [31,41,64,81]. Thorax and pelvis rotations were both larger in stoop lifts compared to those in squat lifts (Fig.…”
Section: Effect Of Lifting Techniquessupporting
confidence: 81%
“…The relative lumbar/pelvic rotations during lowering/ lifting phases showed greater contributions in all cases from the pelvis than the lumbar spine (by as much as twofold) and remained within the range of data reported in the literature [31,41,64,81]. Thorax and pelvis rotations were both larger in stoop lifts compared to those in squat lifts (Fig.…”
Section: Effect Of Lifting Techniquessupporting
confidence: 81%
“…Therefore between hip and spine range of motion in healthy individuals. contrast to some previous reports, our results indicate the absence of correlation between the Findings are in agreement with those of Esola, McClure, Fitzgerald, and Siegler (1996) analysed lumbar and hip motion during forward bending in subject with and without LBP.…”
Section: Discussionsupporting
confidence: 88%
“…In order to get representative information of spine mobility separate assessment of lumbar spine would be recommended as these deliver different/complementary (and flexibility parameters related to trunk movements in different direction is revealed (0.4 < R 2 < different range of motions or everyday activity require forward Therefore, the goal of in healthy individuals. In the absence of correlation between the ald, and Siegler (1996) n subject with and without LBP. lumbar and hip motion in full forward motion.…”
Section: Discussionmentioning
confidence: 98%
“…Marras et al 16 and Thomas et al 31 reported that, compared to women, men move more in the trunk and less in the hips during lifting and forward reaching. These studies focused on gender differences in total motion of the trunk and hips and 4 but to our knowledge, only 1 study has focused specifically on gender differences in movement of the lumbopelvic region. Gombatto et al 9 reported that, compared to women, men with LBP completed a larger percentage of their total lumbopelvic motion in the first 60% of hip lateral rotation range of motion.…”
Section: Discussionmentioning
confidence: 99%